Glomerular Filtration Rate is Associated with Hemorrhagic Transformation in Acute Ischemic Stroke Patients without Thrombolytic Therapy - Ming-Su Liu; Yan Liao; Guang-Qin Li (Chinese Medical Journal, 2018)
Background: Whether there is a relationship between glomerular filtration rate (GFR) and hemorrhagic transformation (HT) after acute ischemic stroke (AIS) is still under debate. The aim of our study was to determine whether the GFR level is a predictor of HT in AIS patients without thrombolytic therapy (TT). Methods: Consecutive AIS patients without TT were included in this prospective study from January 2014 to December 2016 in the First Affiliated Hospital of Chongqing Medical University. We divided them into two groups (HT and non-HT group) and meticulously collected baseline characteristics and laboratory and imaging data of interested individuals. Multivariate regression analysis was performed to assess the correlation between GFR and HT in stroke patients without TT. Results: Among 426 consecutive patients, 74 (17.3%) presented HT (mean age: 65 ± 12 years, number of male patients: 47) on the follow-up scans. In multivariate regression analysis, HT was significantly associated with low GFR (odds ratio [OR] = 3.708, confidence interval [CI] = 1.326–10.693, P = 0.013), atrial fibrillation (AF; OR = 2.444, CI = 1.087–5.356, P = 0.027), large cerebral infarction (OR = 2.583, CI = 1.236–5.262, P = 0.010), and hypoalbuminemia (HA; OR = 4.814, CI = 1.054–22.153, P = 0.037) for AIS patients without TT. Conclusions: The present study strongly showed that lower GFR is an independently predictor of HT; in addition, large infarct volume, AF, and HA are also important risks of HT for AIS patients without TT, which offered a practical information that risk factors should be paid attention or eliminated to prevent HT for stroke patients though the level of evidence seems to be unstable.